2012
DOI: 10.3324/haematol.2011.054437
|View full text |Cite
|
Sign up to set email alerts
|

Impaired expression of DICER, DROSHA, SBDS and some microRNAs in mesenchymal stromal cells from myelodysplastic syndrome patients

Abstract: The online version of this article has a Supplementary Appendix. BackgroundRecent findings suggest that a specific deletion of Dicer1 in mesenchymal stromal cell-derived osteoprogenitors triggers several features of myelodysplastic syndrome in a murine model. Our aim was to analyze DICER1 and DROSHA gene and protein expression in mesenchymal stromal cells (the osteoblastic progenitors) obtained from bone marrow of myelodysplastic syndrome patients, in addition to microRNA expression profile and other target ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 28 publications
2
86
0
Order By: Relevance
“…24 We found that miR-93 and miR-20a expression levels were significantly reduced in MDS-MSC. What is more, overexpression of miR-93/miR-20a reversed cellular senescence in MDS-MSC by targeting p21.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…24 We found that miR-93 and miR-20a expression levels were significantly reduced in MDS-MSC. What is more, overexpression of miR-93/miR-20a reversed cellular senescence in MDS-MSC by targeting p21.…”
Section: Discussionmentioning
confidence: 67%
“…[18][19][20] The ablation of Dicer1 (an RNAse III endonuclease essential for miRNA biogenesis) and the loss of mature miRNA in embryonic fibroblasts and endothelial cells inhibited cell proliferation and induced a premature senescence phenotype. 21,22 Although recent striking findings indicate that Dicer1 deletion can induce an MDS phenotype in mice 23 and that Dicer1 expression is reduced in MSC from MDS patients, 24 the precise mechanism by which the Dicer1 gene contributes to the pathogenesis of MDS remains elusive. We inferred that disordered expression of Dicer1 could contribute to abnormal MSC senescence and impaired stromal support in MDS.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with these notions, it was previously reported that chromosomal abnormalities such as loss of heterozygosity and uniparental disomy (UPD), which can result from doublestranded breaks, are sometimes observed in MSCs derived from AML/MDS patients. [39][40][41] Another possible explanation is that certain factors can directly induce functional abnormality in MSCs. Recently, it was demonstrated that the transplantation of chronic myelogenous leukemia (CML) repopulating cells into immunodeficient mice altered the microenvironmental regulation of the stem cell niche.…”
Section: A B Cmentioning
confidence: 99%
“…Loss of DICER1 in osteoprogenitor cells (but not in mature osteoblasts) resulted in downregulation of the ribosome maturation protein SBDS, which is mutated in human Shwachman-Bodian-Diamond syndrome and is associated with congenital BM failure and leukemic predisposition. 76 Reduced expression of DICER, DROSHA, and SBDS has been noted in BMSCs from patients with MDS, 77 emphasizing the potential clinical relevance of these findings. A recent study has provided mechanistic insight on genotoxic stress caused by mutations in BMSCs, which can impair normal hematopoiesis and favor leukemogenesis.…”
Section: Role Of Bmscsmentioning
confidence: 96%